UTHM E-Voting System Using Blockchain - Mohamed Kassim, Nur Hafizah; Ibrahim, Noraini (Journal of Soft Computing and Data Mining, 2022)
UTHM E-Voting System using Blockchain is a web-based system that develops to enhance and help to improve the efficiency of the existing system and also make the UTHM election process run smoothly and efficiently. In this system, the advantages of blockchain technology are used in the E-Voting system to make it more secure and effective. Lack of security is a primary concern of the current UTHM voting system, such as authentication, confidentiality, integrity, and non-repetition. Besides, the voting process can be inconvenient due to the limited number of polling stations. The distance between these polling stations and college residences causes difficulties for the students to go to a polling station. Moreover, students have to line up for some time before they can vote, which means that some of them leave without even voting. Finally, communication problems cause much misunderstanding between the election council, which is the Jawatankuasa Pemilihan Majlis Perwakilan Pelajar (JPMPP), which leads to an electoral process that cannot function smoothly. Thus, the UTHM E-voting system using blockchain is developed to overcome those problems in this project. The Prototyping Model drives the activities in this project with five main SDLC phases: planning, analysis, design, prototype, and implementation, which are very flexible compared to other software process models. This system is a web-based system that is developed using PHP as programming language and MySQL as database software. This system uses blockchain technology and the ring signature algorithm when conducting and counting the vote to improve the security of the electronic voting system. The test result shows that the system passed 25 of the 25 test cases, accounting for 100% of all the test cases. To conclude, this system is useful because it can improve the efficiency of the entire electoral process compared to the manual system that facilitates the management of the electoral process.